Encephalopathy in a patient with loiasis treated with albendazole: A case report. (April 2020) - Volpicelli, Lorenzo; De Angelis, Maurizio; Morano, Alessandra; Biliotti, Elisa; Franchi, Cristiana; Gabrielli, Simona; Mattiucci, Simonetta; Di Bonaventura, Carlo; Taliani, Gloria
Abstract: Background: Loiasis is a vector-borne parasitic infection endemic across many areas of Central and West Africa. Its treatment is tricky due to the risk of serious neurologic adverse events occurring after the administration of microfilaricidal drugs, like diethylcarbamazine or ivermectin, in subjects with high pre-treatment microfilarial load. Albendazole is currently recommended to slowly reduce microfilaremia before curative regimen is prescribed. Case presentation: We report the case of a 25-year-old man from Guinea-Conakry who was incidentally diagnosed with highly microfilaremic Loa loa infection. A three weeks regimen of albendazole was prescribed. Minor neurologic side effects occurred after two weeks of administration, while serious encephalopathy developed one week later. Clinical and electroencephalographic features of the patient resembled those of an immune-mediated encephalitis. After exclusion of other causes of encephalopathy, treatment-related Loa loa encephalopathy induced by albendazole was suspected. Corticosteroid treatment was administered and the patient recovered. Discussion: Our case confirms that Loa loa treatment-related encephalopathy may occur even during albendazole treatment. The clinical and electroencephalographic similarities between Loa loa albendazole-related encephalopathy and immune-mediated encephalitis suggest the possibility of an underlying inflammation-based pathogenesis. Although corticosteroid administration is not recommended in Loa loa ivermectin-induced encephalopathy, in this case of Loa loa albendazole-induced encephalopathy it may have played a therapeutic role. Highlights: Loa loa treatment-related encephalopathy can occur during albendazole administration. Albendazole-related encephalopathy displays similarities with autoimmune encephalitis. Corticosteroid administration could have played a therapeutic role in this case.